Is the extent of lymphadenectomy a prognostic factor in International Federation of Gynecology and Obstetrics stage II endometrioid endometrial cancer?. Issue 3 (10th January 2021) - Cuylan, Zeliha Firat; Akilli, Huseyin; Gungorduk, Kemal; Demirkiran, Fuat; Oz, Murat; Salman, Mehmet Coskun; Sozen, Hamdullah; Celik, Husnu; Gokcu, Mehmet; Bese, Tugan; Meydanli, Mehmet Mutlu; Ozgul, Nejat; et al.
Abstract: Aim: This study aimed to evaluate the prognostic significance of adequate lymph node dissection (LND) (≥10 pelvic lymph nodes (LNs) and ≥ 5 paraaortic LNs removed) in patients with International Federation of Gynecology and Obstetrics (FIGO) stage II endometrioid endometrial cancer (EEC). Methods: A multicenter department database review was performed to identify patients who had been operated and diagnosed with stage II EEC at seven centers in Turkey retrospectively. Demographic, clinicopathological, and survival data were collected and analyzed. Results: We identified 284 women with stage II EEC. There were 170 (59.9%) patients in the adequate lymph node dissection (LND) group and 114 (40.1%) in the inadequate LND group. The 5‐year overall survival (OS) rate of the inadequate LND group was significantly lower than that of the adequate LND group (84.1% vs. 89.1%, respectively; p = 0.028). In multivariate analysis, presence of lymphovascular space invasion (LVSI) (hazard ratio [HR]: 2.39, 95% confidence interval [CI]: 1.23–4.63; p = 0.009), age ≥ 60 (HR: 3.30, 95% CI: 1.65–6.57; p = 0.001], and absence of adjuvant therapy (HR: 2.74, 95% CI: 1.40–5.35; p = 0.003) remained as independent risk factors for decreased 5‐year disease‐free survival (DFS). Inadequate LND (HR: 2.34, 95% CI: 1.18–4.63; p < 0.001), age ≥ 60 (HR: 2.67, 95% CI: 1.25–5.72; p = 0.011), and absence of adjuvant therapy (HR: 4.95, 95% CI: 2.28–10.73; p < 0.001) were independent prognostic factors for decreased 5‐year OS in multivariate analysis. Conclusion: Adequate LND and adjuvant therapy were significant for the improvement of outcomes in FIGO stage II EEC patients. Furthermore, LVSI was associated with worse 5‐year DFS rate in stage II EEC.